2018
DOI: 10.1186/s12967-018-1723-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of soluble immunoglobulins A and G and their coated bacteria in feces of patients with inflammatory bowel disease

Abstract: BackgroundImmunoglobulin A (IgA) and IgG are major components in human intestinal mucosal surface and sera, and IgA- or IgG-coated bacteria play a vital role in the intestinal homeostasis. However, the correlation of IgA, IgG and their coated bacteria with the clinical characteristics of inflammatory bowel disease (IBD) has not been fully clarified.MethodsThe levels of soluble IgA and IgG in sera and feces were detected by ELISA, and the percentage of IgA- and IgG-coated bacteria in feces was analyzed by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 34 publications
5
54
1
2
Order By: Relevance
“…Inflammation in IBD in humans is thought to be mediated by both cellular and humoral immune mechanisms [68]. Increasingly, studies in IBD in humans (e.g., Crohn’s disease, ulcerative colitis) have focused on the role of immune responses targeted to gut bacteria, as opposed to immune responses targeting gut tissues or dietary antigens [912].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation in IBD in humans is thought to be mediated by both cellular and humoral immune mechanisms [68]. Increasingly, studies in IBD in humans (e.g., Crohn’s disease, ulcerative colitis) have focused on the role of immune responses targeted to gut bacteria, as opposed to immune responses targeting gut tissues or dietary antigens [912].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in humans with IBD have found significantly increased numbers of fecal bacteria with bound IgG, especially in patients with Crohn’s disease (CD) and ulcerative colitis (UC) [12, 18, 19]. It has also been shown in some cases that IBD patients have greater numbers of IgA + bacteria [12, 20]. Interestingly, studies found that the IgG and IgA antibodies preferentially bound to certain pathogenic bacteria in CD patients, including Clostridium coccoides , E .…”
Section: Introductionmentioning
confidence: 99%
“…Opsonization of gut bacteria with IgA even converts anti-inflammatory intestinal CD103 + DCs to a proinflammatory phenotype, which protects against invading pathogens, but might also result in chronic inflammation 5 . Evidence exists that serum IgA contributes to autoimmune diseases, such as inflammatory bowel disease 6,7 , autoimmune skin blistering diseases 8,9 , or rheumatoid arthritis (RA) [10][11][12] as well as to transplant rejection 13 . In addition, IgA has gained interest as a therapeutic antibody against cancer cells, as it activates neutrophilmediated antibody-dependent cellular cytotoxicity better than IgG 14,15 .…”
mentioning
confidence: 99%
“…This observation suggests that AIEC bacteria can be targeted by SIgA in an inflammatory context and that stimulating this pathway could lead to a decrease AIEC load in CD patients. The levels of soluble IgA and the percentage of IgA-coated bacteria strikingly increases in feces of IBD patients and correlates with the disease activity 55 57 . This could be related to an over-activation of IgA-producing mucosal B-cells in response to bacterial stimulus of the adaptive immune system.…”
Section: Discussionmentioning
confidence: 99%